Tobacco consumption and its relation to time taken to death among COVID-19 patients died in an intensive care unit. A retrospective and descriptive study from Mizoram, India - Diki, Lalnun; Vanlalsanga, Joseph C; Fela, Lalrin; Anusuya, Ganesh Shanmugasundaram; Ralte , Jane R; Hnamte, Rebecca Lalruatfeli; Laldinsangi C (Asian Journal of Medical Sciences, 2023)
Background: The relationship between tobacco consumption and coronavirus disease 2019 (COVID-19) deaths among patients admitted in an intensive care unit (ICU) has not been studied in North-east parts of India. Aims and Objectives: The aims and objectives of the present study were to study the prevalence of smoke form and smokeless form of tobacco usage among the patients who had died of COVID-19 and to study the relationship of tobacco usage and number of duration of stay in ICU and number of days taken to death from the time of testing positive. Materials and Methods: This was a retrospective descriptive study of 279 COVID-19-positive patients who got admitted in ICU in Zoram Medical College. Mizoram from February 2020 to February 2022 and subsequently died because of COVID-19 in ICU. The data regarding age, sex, date of testing positive, date of admission in ICU, and date of death were collected from the patient case sheet. The details regarding tobacco consumption were collected from the patients close relatives. Descriptive analysis was carried out by mean and standard deviation along with range for quantitative variables, frequency, and proportion for categorical variables. Data were analyzed using IBM software version 22. P<0.05 was considered as significant. Results: The mean age of the study population was 63.8 years. Majority were males 178 (63.80%). 198 (70.97%) had comorbidities. One hundred and twenty-nine (46.24%) were tobacco users. Mean stay in ICU in days was 7.75 days. Majority were using smokeless form of tobacco 73 (56.59%). The mean duration of survival in days from time tested positive to the death was 39.52 days among tobacco users when compared with non-tobacco users (47.48 days) (P=0.265). Mean duration of survival was 53.07 days among smoke form versus 31.3 days among smokeless form users. (P=0.031). Conclusion: There is no conclusive finding to say that there is a significant difference in time taken to death between tobacco users and non-tobacco users.